Causes of Brains Escape and its Impact on Higher Education in Afghanistan - Aryan, Sebghatullah (Integrated Journal for Research in Arts and Humanities, 2023)
Brains escape, especially the flight of scientific staff from universities and its negative and fatal effect on the education system, is one of the debatable issues in war and post-war countries. Afghanistan is one of the countries that has experienced many years of war and has had the largest number of immigrants to foreign countries, which has created a great void in this country for skilled and educated people. Therefore, in the current research, the causes of brains escape and its effect on the country's higher education are discussed. The central question of the current research was: "What were the causes of brains escape and what effect does it have on the country's higher education?" The prevailing hypothesis in relation to the raised question is that the continuous crises in the country and the lack of attention to the elites and neglecting them as a national value have caused brains escape and affected the education system in the country. The findings of the research show that war, unemployment, poverty, lack of meritocracy are the main factors of brains escape and this process creates a big vacuum in the country's higher education system. Fortunately, recently, with the rise of privileges and members of the scientific staff and providing security ground in the country, the return of elites and scientific staff in the process of education has increase.